Coinfection of hepatitis B and hepatitis C virus among chronic liver disease patients in a tertiary care centre - Dr. Vilas B N.; Dr. Lyra P. R.; Dr. Venkatesha D. (Tropical Journal of Pathology and Microbiology, 2018)
<span style="color: #000000; font-family: ’Times New Roman’; font-size: 19.2px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; letter-spacing: normal; orphans: 2; text-align: justify; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; text-decoration-style: initial; text-decoration-color: initial; font-weight: bold;">Background<span style="color: #000000; font-family: ’Times New Roman’; font-size: 19.2px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: justify; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; text-decoration-style: initial; text-decoration-color: initial; display: inline !important; float: none;">: Hepatitis B virus (HBV) and hepatitis C virus (HCV) are the most common cause of chronic liver disease (CLD) worldwide. Coinfection with both HBV and HCV can occur because of shared routes of infection. Therefore, this study was performed to investigate the seroprevalence of HBV and HCV dual infection among patients attending K R hospital, Mysore with underlying CLD manifestations. <span style="color: #000000; font-family: ’Times New Roman’; font-size: 19.2px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; letter-spacing: normal; orphans: 2; text-align: justify; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; text-decoration-style: initial; text-decoration-color: initial; font-weight: bold;">Materials & Methods:<span style="color: #000000; font-family: ’Times New Roman’; font-size: 19.2px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: justify; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; text-decoration-style: initial; text-decoration-color: initial; display: inline !important; float: none;"> Serum samples from 80 clinically diagnosed chronic liver disease patients attending K R hospital, Mysore was screened for the presence of hepatitis B surface antigen, Anti-HBc IgM, Anti-HBc Ig Gand anti-hepatitis C virus antibodies by ELISA. Serum samples from 15 healthy individuals were also screened. <span style="color: #000000; font-family: ’Times New Roman’; font-size: 19.2px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; letter-spacing: normal; orphans: 2; text-align: justify; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; text-decoration-style: initial; text-decoration-color: initial; font-weight: bold;">Results<span style="color: #000000; font-family: ’Times New Roman’; font-size: 19.2px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: justify; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; text-decoration-style: initial; text-decoration-color: initial; display: inline !important; float: none;">: Among 80 chronic liver disease patients, 67 (83.75%) were males and 13 (16.25%) were females. The maximum number of CLD patients was in the age group of 41 – 50 years (41.30%). Alcoholism (72.5%) was the most common risk fac<span style="color: #000000; font-family: ’Times New Roman’; font-size: 19.2px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: justify; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; text-decoration-style: initial; text-decoration-color: initial; display: inline !important; float: none;">tor & cirrhosis of liver was the most common clinical presentation (81.25%). 38 (47.5%) cases were HBV positive (positive for any one marker for HBV). HBs Ag was positive in 22 cases, anti-HBc Ig Min 7 cases, anti-HBc Ig Gin 29 cases. 4 (5%) cases were positive for anti HCV. Three (3.75%) cases showed coinfection of HBV & HCV. <span style="color: #000000; font-family: ’Times New Roman’; font-size: 19.2px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; letter-spacing: normal; orphans: 2; text-align: justify; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; text-decoration-style: initial; text-decoration-color: initial; font-weight: bold;">Conclusion<span style="color: #000000; font-family: ’Times New Roman’; font-size: 19.2px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: justify; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; text-decoration-style: initial; text-decoration-color: initial; display: inline !important; float: none;">: To prevent the spread of HBV and HCV, people must be educated about these infections and their mode of transmission. All CLD patients should be tested for HBV and HCV to prevent the mortality and morbidity. HBV & HCV coinfection should not be excluded by negative HBsAg status alone.